ENGLISH SPEAKING LEARNINGMANAGEMENTCONDUCTED BY NON-NATIVE JUNIOR HIGH SCHOOL STUDENTS WITH INTERNATIONAL CURRICULUM IN SEMARANG REGENCY - Nur Ekaningsih (Proceedings Education and Language International Conference, 2017)
The objectives of the study are describing in detail of English speaking learning international school plan, the process of English speaking in international classroom and the outcomes of English speaking international students’ capability. This study was done at the pilot project of International school in Semarang Regency, SMP N 1 Ungaran Semarang Regency. This school’s curriculum targeted students competence both in oral and written to resolve daily communicative problems. It is relevant toCahyono and Widiati (2011: 121) that English used in various aspects of life such trade, entertainment, education, governmental diplomacy, science and technology. Therefore, English as the world language will be a significant medium of communication. Using descriptive qualitative approach, this study made an observation, in depth interview and written documents in data collecting. The final findings showed that integrating language skills by combining national and international curriculum creates students’ English broaden speaking expression materials to speak English with longer time learning period. Good learning preparation process in a real world theme affects familiarity and enthusiasm in students’ speaking capability.Consequently, the outcomes related to capability also lookbetter in English speaking. Keywords: English speaking, Non-Native Students, International Curriculum